Effects of the attenuation correction and reconstruction method parameters on conventional cardiac dynamic SPECT. Issue 39 (September 2018) - Mohseni, Mohammadreza; Faghihi, Reza; Haghighatafshar, Mahdi; Entezarmahdi, Seyed Mohammad
Abstract : Abstract: Nuclear cardiology has not witnessed development of new tracers or hardware for many years. Hence there is a need for the development of improvised techniques. Dynamic cardiac single photon emission computed tomography (SPECT) is one such technique that has a potential to overcome the limitations of conventional myocardial SPECT including the absolute quantification of blood flow. The main goal of this study is to evaluate the effect of attenuation correction (AC) on estimation of the washout parameters extracted from dynamic SPECT using a conventional protocol. The effect of the postprocessing on quantitative evaluation of dynamic SPECT is also assessed. A physical phantom was employed to physically simulate the dynamic behavior of a heart in the thorax. Using a dual detector SPECT system, 180° tomographic data in every 90 seconds were acquired. The SPECT data were reconstructed using ordered subset expectation maximization (OSEM) method while different iterations and a Butterworth filter with different cut-off frequencies were applied. Estimated washout parameter of the time activity curves (TACs) was compared with applying AC or without it. Results show that AC can improve the bias of computed washout parameter in normal regions (average bias reduction in normal ROI: 7%). Moreover, the postreconstruction filtering and reducing the number of iterations in reconstructing phase can reduce the variance of the computed washout values in normal regions (from 3.99% for cut-off frequency 0.5 cycle/cm and 32 times update in OSEM to 2.05% for cut-off frequency 0.35 cycle/cm and 16 times update in OSEM). They also reduce the actual size of the defect region (13% reduction in defect extent for above change in reconstruction parameters). According to the results, the AC and postprocessing filtration can directly affect the standard deviation of washout value acquired by cardiac dynamic SPECT. These parameters also showed a direct effect on the defect extent in final results. The study showed that the AC may partly improve the bias of calculated normal washout value. The effect of attenuation correction on the defective washout value could not be answered comprehensively in this paper.